Interaction between β-lactoglobulin and EGCG under high-pressure by molecular dynamics simulation. - Yechuan Huang; Xicai Zhang; Huayi Suo (PLoS ONE)
The binding between β-lactoglobulin and epigallocatechin gallate (EGCG) under the pressure of 600 MPa was explored using molecular docking and molecular dynamics (MD) simulation. EGCG bound mainly in two regions with site 1 in internal cavity of the β-barrel and site 2 on the surface of protein. 150 ns MD was performed starting from the structure with the optimal binding energy at the two sites in molecular docking, respectively. It was found that the protein fluctuated greatly when small molecule bound to site 2 at 0.1 MPa, and the protein fluctuation and solvent accessible surface area became smaller under high-pressure. The binding of small molecules made the protein structure more stable with increasing of α-helix and β-sheet, while high-pressure destroyed α-helix of protein. The binding energy of small molecules at site 1was stronger than that at site 2 under 0.1 MPa, with stronger van der Waals and hydrophobic interaction at site 1 while more hydrogen bonds were present at site 2. The binding energy of both sites weakened under high-pressure, especially at site 1, causing the binding force to be weaker at site 1 than that at site 2 under high-pressure.